2014
DOI: 10.1007/s10665-014-9699-0
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning strategies for the block Cimmino algorithm

Abstract: Science and Technology Facilities Council preprints are available online at: http://epubs.stfc.ac.uk ABSTRACT In the context of the block Cimmino algorithm, we study preprocessing strategies to obtain block partitionings that can be applied to general linear systems of equations Ax = b. We study strategies that transform the matrix AA T into a matrix with a block tridiagonal structure. This provides a partitioning of the linear system for row projection methods because block Cimmino is essentially equivalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…One alternative variation is the block Cimmino [7] which is a block row projection method. Iterative block Cimmino has been studied extensively in [7,9,14,17,23,25,26]. A pseudo-direct version of block Cimmino based on the augmented block row projections is proposed in [24].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…One alternative variation is the block Cimmino [7] which is a block row projection method. Iterative block Cimmino has been studied extensively in [7,9,14,17,23,25,26]. A pseudo-direct version of block Cimmino based on the augmented block row projections is proposed in [24].…”
mentioning
confidence: 99%
“…It is also reported that the CG accelerated Cimmino method competes favorably compared to classical preconditioned Generalized Minimum Residual (GMRES) and Conjugate Gradient on Normal Equations (CGNE) for the solution of nonsymmetric linear systems that arise in an elliptic partial differential equation. On the other hand, it should be noted that the main motivation of block Cimmino algorithm is its amenability of parallelism [23].…”
mentioning
confidence: 99%
See 3 more Smart Citations